2014
DOI: 10.2337/db13-1961
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Expression and Cavin Stability Regulate Caveolae Dynamics in Adipocyte Lipid Store Fluctuation

Abstract: Adipocytes specialized in the storage of energy as fat are among the most caveolae-enriched cell types. Loss of caveolae produces lipodystrophic diabetes in humans, which cannot be reversed by endothelial rescue of caveolin expression in mice, indicating major importance of adipocyte caveolae. However, how caveolae participate in fat cell functions is poorly understood. We investigated dynamic conditions of lipid store fluctuations and demonstrate reciprocal regulation of caveolae density and fat cell lipid dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 51 publications
4
58
2
1
Order By: Relevance
“…Expression and distribution of Cavins might be affected whereas Caveolin-1 distribution or expression seems unaltered but still leads to caveolae disassembly. Briand et al have recently reported that during extreme fat cell shrinkage in adipocytes, Caveolin-1 expression was unaffected whereas Cavins were targeted to degradation resulting in caveolae disassembly (64). The deletion of Cavin-2 in endothelial cells causes flattening of caveolae perturbing neither Caveolin-1 expression nor oligomerization (65).…”
Section: Discussionmentioning
confidence: 98%
“…Expression and distribution of Cavins might be affected whereas Caveolin-1 distribution or expression seems unaltered but still leads to caveolae disassembly. Briand et al have recently reported that during extreme fat cell shrinkage in adipocytes, Caveolin-1 expression was unaffected whereas Cavins were targeted to degradation resulting in caveolae disassembly (64). The deletion of Cavin-2 in endothelial cells causes flattening of caveolae perturbing neither Caveolin-1 expression nor oligomerization (65).…”
Section: Discussionmentioning
confidence: 98%
“…119 In adipose cell lines and mice, expression of Cav1 is crucial to increase the density of caveolae, to increase the ability of adipocytes to accommodate large lipid droplets and to promote cell expansion by increased glucose utilization. 120 Caveolin proteins bind cholesterol, and the protein's ability to move between cellular compartments helps control intracellular cholesterol fluxes. 121 A homozygous nonsense mutation in CAV1 has been reported in a 20yearold woman from Brazil with generalized lipodystrophy, short stature, functional megaoesophagus and hypocalcaemia, which was pre sumed to be secondary to vitamin D resistance.…”
Section: Type 3 Cglmentioning
confidence: 99%
“…Adenovirus was obtained by recombination of viral backbones with shuttle vectors containing DAPK2 cDNAs and packaging in complementing 293 cells, as described previously (14). GFP-LC3 3T3-L1 stable transfectants were obtained as described (15). Human preadipocytes were isolated from subcutaneous adipose tissue and cultured as described (16).…”
Section: Cell Culturementioning
confidence: 99%